Biogeographical and seasonal distribution of pteropod populations in the western and central Mediterranean Sea inferred from sediment traps - Béjard, Thibauld M.; Manno, Clara; Sierro, Francisco J.; Flores, José-Abel; Tarruella, Javier P.; de Madron, Xavier Durrieu; Sanchez-Vidal, Anna; Rigual-Hernández, Andrés S. (Frontiers in Marine Science, 2024)
Pteropods are a group of cosmopolitan holoplanktic gastropods that produce an aragonite shell and play an important role in both marine ecosystems and geochemical cycles. In addition to being affected by anthropogenic impacts that include warming and changes in carbonate system parameters, the Mediterranean Sea is considered to be understudied concerning pteropods dynamics and abundances. This work aims to document the modern spatial and temporal distributions of pteropods populations in the Northwestern and Central Mediterranean Sea (Gulf of Lions and Strait of Sicily), respectively. We present data from two sediment-trap records that cover the timeframe between early 1996 and early 2004 for the Gulf of Lions and late 2013 to late 2014 for the Sicily Strait. A total of 843 pteropod shells and 18 different species were identified. Limacina inflata, Creseis virgula and Creseis clava were the most abundant species in the Gulf of Lions, while in the Sicily Strait, C. conica replaced C. clava as the most abundant species. These taxons represented around 70% of the total individuals identified in both sites. Overall, our results suggest a greater pteropod abundance in the Gulf of Lions than in the Sicily Strait, most likely due to enhanced food conditions. In the Gulf of Lions, maximum fluxes occurred in autumn (32.5% of the annual pteropod fluxes registered in October), while in the Sicily Strait peak fluxes occurred in winter (30.5% of the annual pteropod fluxes registered in January). Comparison of temporal changes pteropod fluxes with satellite sea surface temperature (SST), and chlorophyll-a concentration suggest a possible positive effect of high algal accumulation and cool water conditions in the Strait of Sicily on the main pteropod groups. In turn, no clear relationships between pteropod groups, SST and chlorophyll-a were identified in the Gulf of Lions, highlighting the effect of salinity and carbonate system parameters. Overall, and despite the limitations associated with the use of sediment traps for pteropod population monitoring, the consistency of our results with the literature supports the use of sediment traps as useful tools for documenting the diversity and temporal distribution of pteropods.